2009
DOI: 10.1039/b815549f
|View full text |Cite
|
Sign up to set email alerts
|

Sugar nucleotide recognition by Klebsiella pneumoniae UDP-d-galactopyranose mutase: Fluorinated substrates, kinetics and equilibria

Abstract: A series of selectively fluorinated and other substituted UDP-D-galactose derivatives have been evaluated as substrates for Klebsiella pneumoniae UDP-D-galactopyranose mutase. This enzyme, which catalyses the interconversion of the pyranose and furanose forms of galactose as its UDP adduct, is a prospective drug target for a variety of microbial infections. We show that none of the 2''-, 3''- or 6''-hydroxyl groups of UDP-D-galactopyranose are essential for substrate binding and turnover. However, steric facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 57 publications
2
26
1
Order By: Relevance
“…The 2-, 3-and 6-monofluorosubstituted UDP-Galp analogs, as well as the 2-and 3-and 6-monofluoro-substituted UDP-Galf analogs were found to be substrates for UGM. [32][33][34][35][36] In addition, UDP-D-talopyranose (C2 hydroxyl in axial orientation) and UDP-2-deoxy-2-fluoro-D-talopyranose (2-fluoro in axial orientation) are not substrates of UGM. 34 Recently N'Go et al 37 reported the synthesis of dideoxy-tetrafluorinated analogs of both UDP-Galp (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-Dthreo-hexopyranose 3, abbreviated as UDP-F 4 -Galp) and UDP-Galf (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-D-threo-hexofuranose 4, abbreviated as UDP-F 4 -Galf) and shown that these dideoxytetrafluorinated analogs are excellent inhibitors, but not substrates of UGM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-, 3-and 6-monofluorosubstituted UDP-Galp analogs, as well as the 2-and 3-and 6-monofluoro-substituted UDP-Galf analogs were found to be substrates for UGM. [32][33][34][35][36] In addition, UDP-D-talopyranose (C2 hydroxyl in axial orientation) and UDP-2-deoxy-2-fluoro-D-talopyranose (2-fluoro in axial orientation) are not substrates of UGM. 34 Recently N'Go et al 37 reported the synthesis of dideoxy-tetrafluorinated analogs of both UDP-Galp (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-Dthreo-hexopyranose 3, abbreviated as UDP-F 4 -Galp) and UDP-Galf (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-D-threo-hexofuranose 4, abbreviated as UDP-F 4 -Galf) and shown that these dideoxytetrafluorinated analogs are excellent inhibitors, but not substrates of UGM.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] In addition, UDP-D-talopyranose (C2 hydroxyl in axial orientation) and UDP-2-deoxy-2-fluoro-D-talopyranose (2-fluoro in axial orientation) are not substrates of UGM. 34 Recently N'Go et al 37 reported the synthesis of dideoxy-tetrafluorinated analogs of both UDP-Galp (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-Dthreo-hexopyranose 3, abbreviated as UDP-F 4 -Galp) and UDP-Galf (UDP-2,3-dideoxy-2,2,3,3-tetrafluoro-D-threo-hexofuranose 4, abbreviated as UDP-F 4 -Galf) and shown that these dideoxytetrafluorinated analogs are excellent inhibitors, but not substrates of UGM. The rationale for the introduction of this unusual fluorination motif originated from studies 38,39 in which affinity gain is sought through a combination of favourable hydrophobic desolvation energy and atractive multipolar interactions of the C-F groups with protein residues (with such interactions being negligible in aqueous medium).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the biosynthesis of these other hexofuranose sugars. Previous work has established that the UGM from K. pneumoniae, which has been the most studied, is unable to catalyze the synthesis of either UDP-Fucf or UDP-GalfNAc (26,34). Recently it has been shown that a homologue of the glf gene, fcf2 in E. coli O52, acts as a Fucf mutase enzyme for the biosynthesis of TDPFucf (35).…”
mentioning
confidence: 99%
“…This arginine appears to stabilize the negatively charged diphosphate backbone of the sugar nucleotide substrate. Many synthetic analogues (21)(22)(23)(24)(25)(26) have been used to probe the mechanism of UGM and investigate substrate binding, but until recently, no ligand-bound crystal structures have been available. Tryptophan fluorescence (15) and molecular modeling have predicted that the uridine of the UDP-Gal base stacks with Trp-160 (numbering for K. pneumoniae) (27); in contrast, recent crystal structures of the K. pneumoniae UGM with bound UDP-Glcp (28) and UDP-Galp (29) show that the uridine stacks against tyrosine 155 in the active site.…”
mentioning
confidence: 99%
“…Analytes were eluted using mobile phase A: formic acid 0.3% brought to pH 9.0 with ammonia and mobile phase B: acetonitrile using the following multistep gradient at a flow rate 80 ”L/min: 0 min: 2% B; 20 min: 15% B; 26 min: 50% B; 27 min: 90% B; 30 min: 90% B; 31 min: 2% B; 50 min: 2% B. Available sugar nucleotide standards (10 ”M) were injected (5 ”L) to determine retention time (Table S2) [37] and UDP-ÎČ-L-Arap [38] were prepared as previously described. Although between runs there were significant differences in absolute retention times of standards, relative retentions were reasonably reproducible (Table S2).…”
Section: Sugar Nucleotide Profilingmentioning
confidence: 99%